background image

h

=

def

I

B

FCD

(

B

)

f

I

A

FCD

(

A

)

. For every

X ∈

A

h

h

iX

=

D

I

B

FCD

(

B

)

E

h

f

i

D

I

A

FCD

(

A

)

E

X

=

B ∩

B

h

f

i

(

A ∩

A

X

)

.

From this, as easy to show,

h

f

and

h

⊆ A ×

FCD

B

. If

g

f

g

⊆ A ×

FCD

B

for a

g

FCD

(

A

;

B

)

then dom

g

⊆ A

, im

g

⊆ B

,

h

g

iX

=

B ∩

B

h

g

i

(

A ∩

A

X

)

⊆ B ∩

B

h

f

i

(

A ∩

A

X

) =

D

I

B

FCD

(

B

)

E

h

f

i

D

I

A

FCD

(

A

)

E

X

=

h

h

iX

,

g

h

. So

h

=

f

FCD

(

A

;

B

)

(

A ×

FCD

B

)

.

Corollary 62.

Let

A

,

B

are sets of filters over boolean lattices. For every

f

FCD

(

A

;

B

)

and

A ∈

A

we have

f

|

A

=

f

(

A ×

FCD

1

B

)

.

Proof.

f

(

A ×

FCD

1

B

) =

I

1

B

FCD

(

B

)

f

I

A

FCD

(

A

)

=

f

I

A

FCD

(

A

)

=

f

|

A

.

Corollary 63.

Let

A

,

B

are sets of filters over boolean lattices. For every

f

FCD

(

A

;

B

)

and

A ∈

A

,

B ∈

B

we have

f

FCD

(

A

;

B

)

(

A ×

FCD

B

)

0

FCD

(

A

;

B

)

⇔ A

[

f

]

B

.

Proof.

f

FCD

(

A

;

B

)

(

A ×

FCD

B

)

0

FCD

(

A

;

B

)

f

FCD

(

A

;

B

)

(

A ×

FCD

(

A

;

B

)

B

)

1

A

0

B

D

I

B

FCD

(

B

)

f

I

A

FCD

(

A

)

E

1

A

0

B

D

I

B

FCD

(

B

)

E

h

f

i

D

I

A

FCD

(

A

)

E

1

A

0

B

⇔ B ∩

B

h

f

i

(

A ∩

A

1

A

)

0

B

B ∩

B

h

f

iA

0

B

⇔ A

[

f

]

B

.

Theorem 64.

Let

A

,

B

are sets of filters over boolean lattices. Then the poset

FCD

(

A

;

B

)

is

separable.

Proof.

Let

f , g

FCD

(

A

;

B

)

and

f

g

. By the theorem 12

[

f

]

[

g

]

. That is there exist

x, y

A

such

that

x

[

f

]

y

<

x

[

g

]

y

that is

f

FCD

(

A

;

B

)

(

x

×

FCD

y

)

0

FCD

(

A

;

B

)

<

g

FCD

(

A

;

B

)

(

x

×

FCD

y

)

0

FCD

(

A

;

B

)

.

Thus

FCD

(

A

;

B

)

is separable.

Theorem 65.

Let

(

A

;

Z

0

)

and

(

B

;

Z

1

)

are primary filtrators over boolean lattices. If

S

P

(

A

×

B

)

then

\

FCD

(

A

;

B

)

{A ×

FCD

B |

(

A

;

B

)

S

}

=

\

A

dom

S

×

FCD

\

B

im

S.

Proof.

If

x

atoms

A

then by the theorem 56

 \

FCD

(

A

;

B

)

{A ×

FCD

B |

(

A

;

B

)

S

}

x

=

\

B

{hA ×

FCD

Bi

x

|

(

A

;

B

)

S

}

.

If

x

A

T

A

dom

S

0

A

then

(

A

;

B

)

S

: (

x

A

A

0

A

A ×

FCD

(

A

;

B

)

B

x

=

B

);

{hA ×

FCD

B i

x

|

(

A

;

B

)

S

}

=

im

S

;

if

x

A

T

A

dom

S

= 0

A

then

(

A

;

B

)

S

: (

x

A

A

= 0

A

∧ hA ×

FCD

Bi

x

= 0

B

);

{hA ×

FCD

Bi

x

|

(

A

;

B

)

S

} ∋

0

B

.

So

 \

FCD

(

A

;

B

)

{A ×

FCD

B |

(

A

;

B

)

S

}

x

=

(

T

B

im

S

if

x

A

T

A

dom

S

0

A

;

0

B

if

x

A

T

A

dom

S

= 0

A

.

From this by corollary 53 (taking in account 47 in [3]) follows the statement of the theorem.

Corollary 66.

Let

(

A

;

Z

0

)

and

(

B

;

Z

1

)

are primary filtrators over boolean lattices.

Pointfree funcoids

13